Influence of graphite/alumina on co-pyrolysis of Chlorella vulgaris and polypropylene for producing bio-oil. (15th February 2023) - Chen, Chunxiang; Zhao, Jian; Wei, Yixue; Huang, Xiaodong; Lu, Wei; Fan, Dianzhao; Bi, Yingxin; Qiu, Hongfu
Abstract: The effects of Graphite/Alumina (GP/Al2 O3 ) compound additives with different addition amounts (10%, 20%, 30% and 40%) and different mixing ratios (10:0, 7:3, 5:5, 3:7 and 0:10) on co-pyrolysis characteristics, product yield and bio-oil components of Chlorella vulgaris (CV) and polypropylene (PP) were studied by microwave thermogravimetry and GC-MS. The results indicated that compared with the C8P2 (CV:PP = 8:2) group, 30% G10A0 (GP:Al2 O3  = 10:0) could greatly improve pyrolysis efficiency, but the contents of hydrocarbons and alcohols in bio-oil decreased and the content of acids increased. 40% G0A10 could increase the content of hydrocarbons and decrease the content of phenols in bio-oil, but the yield of bio-oil was 3.16% lower than that of C8P2 group. For 40% compound additive groups, GP/Al2 O3 could increase the production of bio-oil without increasing energy consumption, and the contents of hydrocarbons and alcohols in bio-oils increased. The maximum contents of hydrocarbons and alcohols appeared in the 40% G7A3 group, 29.56% and 34.60% respectively. In addition, alkyl-cyclohexane accounted for 65.95% of hydrocarbons in 40% G7A3 group. Therefore, the content of alkyl-cyclohexane can be controlled purposefully to be used in chemical fields such as organic synthesis and preparation of antistatic coatings, so as to expand the application of bio-oil. Graphical abstract: Image 1 Highlights: Co-pyrolysis of CV and PP under Graphite/Alumina additives were studied. Graphite/Alumina increased bio-oil yields by 20–60% and reduced gas yields by 5–10%. More hydrocarbons and alcohols appeared in bio-oil under the compound additives. Alkyl-cyclohexane reached to 65.95% of hydrocarbons in 40% G7A3.